Associate Professor Ts. Dr. Devarajan developed a Bio Hybrid eco friendly engine coolant - Nur Hartini, Mohd Hatta (2022)
PEKAN, 17 March 2022 – In order to create a more efficient engine, various researches have been done in relation to engine coolant.